Fosmanogepix (APX001) Is Effective in the Treatment of Pulmonary Murine Mucormycosis Due to Rhizopus arrhizus - Gebremariam, Teclegiorgis (Antimicrob Agents Chemother, 2020)
Mucormycosis is a life-threatening infection with high mortality that occurs predominantly in immunocompromised patients. Manogepix (MGX) is a novel antifungal that targets Gwt1, a protein involved in an early step in the conserved glycosylphosphotidyl inositol (GPI) posttranslational modification pathway of surface proteins in eukaryotic cells. Inhibition of fungal inositol acylation by MGX results in pleiotropic effects, including inhibition of maturation of GPI-anchored proteins necessary for growth and virulence. MGX has been previously shown to have in vitro activity against some strains of Mucorales. Here, we assessed the in vivo activity of the prodrug fosmanogepix, currently in clinical development for the treatment of invasive fungal infections, against two Rhizopus arrhizus strains with high (4.0 μg/ml) and low (0.25 μg/ml) minimum effective concentration (MEC) values. In both invasive pulmonary infection models, treatment of mice with 78 mg/kg or 104 mg/kg fosmanogepix, along with 1-aminobenzotriazole to enhance the serum half-life of MGX in mice, significantly increased median survival time and prolonged overall survival by day 21 postinfection compared to placebo. In addition, administration of fosmanogepix resulted in a 1 to 2 log reduction in both lung and brain fungal burden. For the 104 mg/kg fosmanogepix dose, tissue clearance and survival were comparable to clinically relevant doses of isavuconazole (ISA), which is FDA approved for the treatment of mucormycosis. These results support continued development of fosmanogepix as a first-in-class treatment for invasive mucormycosis.